Angiofibroma Originating outside the Nasopharynx: A Management Dilemma - Ashraf Nabeel Mahmood; Rashid Sheikh; Hamad Al Saey; Sarah Ashkanani; Shanmugam Ganesan (Case Reports in Otolaryngology)
Background. Angiofibroma is a benign tumor, consisting of fibrous tissue with varying degrees of vascularity, characterized by proliferation of stellate and spindle cells around the blood vessels. It most commonly arises from the nasopharynx, although it may rarely arise in extranasopharyngeal sites. Case Report. A 46-year-old male presented with left side nasal obstruction and epistaxis for one month. Clinical nasal examination revealed left sided polypoidal mass arising from the vestibular region of the lateral nasal wall. Results. CT scan and MRI showed highly vascular soft tissue mass occupying the anterior part of the left nostril. Preoperative selective embolization followed by transnasal excision was performed. Histopathological examination confirmed the diagnoses of nasal vestibular angiofibroma. Conclusion. Extranasopharyngeal angiofibroma is a very rare pathology. It should be kept in mind as a differential diagnosis with any unilateral nasal vestibular mass causing nasal obstruction and epistaxis. A biopsy without further investigation can cause life threatening bleeding in the patient.